Innovative Strategies for Preserving the Javanese Language Among Youth: Integrating Digital Technology and Multicultural Education in the Postmodern Era - Dyah Ayu Setyo Astuti; Salma Fitriani; Zumala'in Nuriyasari; Much Arsyad Fardani (Journal of Education and Teacher Development, 2025)
The Javanese language is facing a critical decline among younger generations due to the accelerating forces of globalization and digitalization. This study investigates the current landscape, contributing factors to language attrition, and proposes innovative strategies for language preservation through the integration of digital technology and multicultural education within a postmodern context. Employing a Systematic Literature Review (SLR), the study synthesizes findings from 20 high-quality articles selected from an initial pool of 156 publications spanning the years 2019 to 2024. The results reveal that 40% of existing research emphasizes digital technology, with five primary causes of language decline identified: the dominance of digital media, weak intergenerational transmission, misaligned pedagogical approaches, social stigma, and the pervasive impact of globalization. Effective strategies include the promotion of digital literature, audiovisual learning media, digital learning platforms, and interactive storytelling. The study culminates in a Holistic Integration Model comprising five interrelated pillars: adaptive digital technology, transformative education, popular culture communities, regulatory policy frameworks, and continuous monitoring and evaluation. These components collectively support the development of a sustainable ecosystem for Javanese language revitalization.